Factors that Influence First-year Students’ Academic Performance in Introductory Accounting: A Systematic Literature Review and Avenues for Future Research - Joynt, Corlia (International Journal of African Higher Education, 2023)
This study involved a systematic review of academic research conducted between 1968 and 2022 on the factors that predict academic performance in introductory accounting. Several significant predictors including prior knowledge in accounting, academic aptitude and mathematical ability, as well as personal attributes like grit and self-efficacy have been shown to influence student success in this field. The study’s findings will assist educators to adapt their programmes and integrate these predictive factors. Moreover, this research expands on the theoretical framework established by Rankin, Silvester, Wallely and Wyatt (2003), offering a holistic perspective and highlighting potential areas that warrant further investigation. Future research could explore the role of critical reasoning skills and reading comprehension’s impact as predictors of academic performance in introductory accounting.